2019
DOI: 10.1080/17434440.2019.1610387
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence (AI) for the early detection of breast cancer: a scoping review to assess AI’s potential in breast screening practice

Abstract: Introduction: Various factors are driving interest in the application of artificial intelligence (AI) for breast cancer (BC) detection, but it is unclear whether the evidence warrants large-scale use in population-based screening. Areas covered: We performed a scoping review, a structured evidence synthesis describing a broad research field, to summarize knowledge on AI evaluated for BC detection and to assess AI's readiness for adoption in BC screening. Studies were predominantly small retrospective studies b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(89 citation statements)
references
References 45 publications
0
76
0
1
Order By: Relevance
“…First, the reader study was done with a cancer-enriched dataset, which has different cancer prevalence to real-field data (50% in the reader study dataset vs <1% in real-field data). Medical AI has been increasingly studied as deep learning technology becomes mainstream, but most studies have methodological deficiencies 15,16 -eg, in a systematic review of deep learning performance in medical imaging, only four of 82 studies considered diagnostic performance in an algorithm-plus-clinician scenario. 15 Although our study compared the diagnostic performance of humans, AI-aided humans, and standalone AI using an independent set of external data in a strict reader study format, the real clinical value needs to be investigated further via prospective clinical studies with the same prevalence of the real-world clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…First, the reader study was done with a cancer-enriched dataset, which has different cancer prevalence to real-field data (50% in the reader study dataset vs <1% in real-field data). Medical AI has been increasingly studied as deep learning technology becomes mainstream, but most studies have methodological deficiencies 15,16 -eg, in a systematic review of deep learning performance in medical imaging, only four of 82 studies considered diagnostic performance in an algorithm-plus-clinician scenario. 15 Although our study compared the diagnostic performance of humans, AI-aided humans, and standalone AI using an independent set of external data in a strict reader study format, the real clinical value needs to be investigated further via prospective clinical studies with the same prevalence of the real-world clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the first studies of AI for breast cancer detection showed that these were predominantly retrospective studies based on relatively small and narrowly selected (i.e., cancer-enriched) imaging data sets as well as heterogeneous AI techniques. Most studies validated developed models, and rather few tested models on independent datasets [6].…”
Section: Where Does Ai Come In?mentioning
confidence: 99%
“…AI algorithms should be expanded to cover other fields of breast imaging with huge amounts of data such as digital breast tomosynthesis, MRI, and automated 3D US. Moreover, future research will have to deal with the acceptability of using AI in breast cancer screening services and the many ethical, social, and legal implications of their use [6]. Computers cannot be held accountable, but radiologists applying AI algorithms for reporting will be.…”
Section: Where Do We Go From Here?mentioning
confidence: 99%
“…Houssami et al [45] exploring different AI methods in breast cancer detection. Authors are pinpoint the recent gaps in the clinical translation of AI systems into regular breast cancer screening practice.…”
Section: Related Workmentioning
confidence: 99%